Osteoporosis - Marcus, Robert, 1940-; Feldman, David, 1939-; Dempster, David W.; Luckey, Marjorie; Cauley, Jane A. (ClinicalKey., 2013)
Now in its third edition, Osteoporosis, is the most comprehensive, authoritative reference on this disease. Written by renowned experts in the field, this two-volume reference is a must-have for academic and medical libraries, physicians, researchers, and any company involved in osteoporosis research and development. Worldwide, 200 million women between 60-80 suffer from osteoporosis and have a lifetime risk of fracture between 30 and 40 % continuing to make osteoporosis a hot topic in medicine.